Harnessing Tumor Cell‐Derived Exosomes for Immune Rejection Management in Corneal Transplantation - Jieru Yang; Huanmin Kang; Yingyi Liu; Shan Lu; Huihui Wu; Bikui Zhang; Yan He; Wenhu Zhou (Advanced Science)
Abstract Transplantation remains the definitive treatment for end‐stage organ failures, but its efficacy is frequently compromised by immune rejection. This study introduces a novel strategy by utilizing tumor‐derived exosomes from B16‐F10 melanoma cells (B16‐Exo), diverging from the conventional use of immune cell‐derived exosomes, to alleviate post‐transplantation immune rejection. Utilizing murine corneal transplantation as a model, it is demonstrated that B16‐Exo significantly reduces immune rejection, evidenced by decreased corneal opacity, neovascularization, and immune dysregulation, while enhancing postoperative survival. Proteomic analyses reveal differential expression of pivotal proteins in B16‐Exo, notably the JAK2 protein within the JAK‐STAT signaling pathway, which has been mechanistically demonstrated to amplify the activity of myeloid‐derived suppressor cells (MDSCs) and inhibit T cell proliferation. These findings demonstrate the significant immunomodulatory effect of B16‐Exo in transplant immunology, supporting the continued exploration of tumor‐derived exosomes as a platform to uncover novel immunosuppressive mechanisms in transplantation.